Personalized Learning Systems: Essential Components and Their Impact on Learning Outcomes - Ubaidah; Basuki Wibawa; Murti Wirasti (Je-LKS: Journal of E-Learning and Knowledge Society)
Personalized learning has emerged as a promising approach to meet the diverse needs of learners. Personalized learning flexibly provides various learning options to suit learners’ needs and learning speed. Instructional designers and researchers need directions regarding the components of a personalized learning system that can support achieving learning objectives. Many researchers propose personalized learning components only to identify the characteristics of personalized learning. This paper explores and elucidates the key components of personalized learning as an instructional system to ensure the achievement of learning objectives. The research method used is a systematic literature review. This study reviews related literature to analyze the personalized learning system's input, process, and output components. We included literature that proposes personalized learning models in various application and experimental contexts to see the personalized learning components used and their impact. After the identification and screening process, we reviewed eligible works of literature. We proposed a conclusion that there are five components of personalized learning: 1) learner profile, 2) learning objectives, 3) learning path, 4) learning environment, and 5) learning result. This research recommends future research on personalized learning to measure and ensure the achievement of learning objectives with personalized learning.